Bond Strength and Surface Roughness of Two Ceramics After Metal Bracket Debonding - Luciana P.B. Arcas; Kusai Baroudi; Caroline A.B. de Matos; Fabiana C. Ribeiro; Laís R. Silva-Concílio; Marina Amaral (Galenos Yayinevi, 2023)
Objective:The aims of this study were to compare the bond strength between metallic brackets and two different glass ceramics and to evaluate the ceramic surface roughness after different finishing protocols.Methods:The surface roughness of lithium disilicate and resin matrix ceramic samples was measured (initial). All samples were treated with hydrofluoric acid and silane and bonded to metallic brackets with orthodontic cement adhesive. Shear bond strength tests were performed using a universal testing machine (n=12). The surface roughness was measured again (intermediate, n=6) after removing the remaining cement adhesive from the ceramic surfaces with a diamond or 24-blade bur after polishing the ceramic surfaces (final, n=6).Results:The resin matrix ceramic had the highest bond strength. The rotatory instrument used for the removal of cement adhesive did not affect the surface roughness of the resin matrix ceramic or lithium disilicate (p=0.985 and p=0.504, respectively), but did affect the evaluation time (p<0.001) for both restorative materials. The intermediate roughness was the highest. For the resin matrix ceramic, polishing promoted a final surface roughness similar to the initial condition; however, changes in the surface shape of this ceramic could be visibly observed when using a 24-blade bur.Conclusion:The bond strength of metallic brackets bonded on resin-matrix ceramics is higher than bonding on lithium disilicate. The use of diamond burs for the removal of the remaining adhesive from the resin matrix ceramics is highly recommended.